Gus and Grandpa and the two-wheeled bike - Mills, Claudia (Farrar, Straus and Giroux, 1999)
Gus doesn't want to give up the training wheels on his bike, even for a new five-speed bicycle, until Grandpa helps him learn how to get along without them.